Tìm kiếm trong hệ cơ sở dữ liệu tên họ latin - Nam, Phương Minh (Journal of Computer Science and Cybernetics, 2016)
The purpose of this paper to examine the first-name and family-names indentification problem in database for person’s management. Some algorithms are proposed, based on errors probability of occurrences of alphabets and frequence of occurrences of alphabets in the first and family-names in database. It is shown that these algorithms are very effective in application.